Goldfish phoenixin: (I) structural characterization, tissue distribution, and novel function as a feedforward signal for feeding-induced food intake in fish model - Qin, Xiangfeng; Ye, Cheng; Chan, Ying Wai; Wong, Anderson O. L. (Frontiers in Endocrinology, 2025)
Phoenixin (PNX) is a novel peptide with diverse functions mediated by the orphan receptor GPR173. It also plays a role in appetite control, but the effect is not consistent across species and the mechanisms involved are still unclear. Using goldfish as a model, the mechanisms underlying feeding regulation by PNX were examined. In our study, two isoforms of PNX, PNXa and PNXb, and one form of GPR173 were cloned in goldfish and found to be highly conserved compared to their counterparts in other species based on sequence alignment, phylogenetic analysis, and in silico protein modeling. Using RT-PCR, PNXa/b and GPR173 were confirmed to be ubiquitously expressed at the tissue level. In goldfish, transcript expression of PNXa/b and GPR173 in the liver and brain areas including the telencephalon, hypothalamus, and optic tectum, were elevated by food intake but suppressed by fasting. Intraperitoneal (IP) and intracerebroventricular (ICV) injections of PNX20a and PNX20b, the mature peptides for PNXa and PNXb respectively, were both effective in increasing foraging behavior, surface motility, and food intake. Furthermore, the expression of orexigenic factors (neuropeptide Y (NPY), agouti-related peptide, orexin, and apelin) was elevated with parallel drops in anorexigenic signals (cholecystokinin, pro-opiomelanocortin, corticotropin-releasing hormone, and melanin-concentrating hormone) in the telencephalon, hypothalamus, and/or optic tectum. In the same brain areas, receptor expression for anorexigenic factors (leptin and adiponectin) was attenuated with concurrent rises in receptor levels for orexigenic signals (NPY and ghrelin). In our study, after IP injection of PNX20a/b, downregulation of leptin, adiponectin, and other feeding inhibitors expressed in the liver was also noted. Our findings reveal that PNX20a/b can serve as an orexigenic factor in goldfish. PNX signals (both central and peripheral) can be induced by food intake and act within the brain to trigger foraging and food consumption via differential modulation of appetite-regulating factors and their receptors in different brain areas. The feeding responses observed may also involve a hepatic component with PNX repression of feeding inhibitors expressed in the liver. The PNX signals induced by feeding may form a feedforward loop to maintain/prolong food intake during a meal prior to the onset of satiation response in our fish model.